Fossil fuel-related emissions were the major source of NH3 pollution in urban cities of northern China in the autumn of 2017. (January 2020) - Zhang, Zhongyi; Zeng, Yang; Zheng, Nengjian; Luo, Li; Xiao, Hongwei; Xiao, Huayun
Abstract: As the most important gas-phase alkaline species, atmospheric ammonia (NH3 ) contributes considerably to the formation and development of fine-mode particles (PM2.5 ), which affect air quality and environmental health. Recent satellite-based observations suggest that the North China Plain is the largest agricultural NH3 emission source in China. However, our isotopic approach shows that the surface NH3 in the intraregional urban environment of Beijing-Tianjin-Shijiazhuang is contributed primarily by combustion-related processes (i.e., coal combustion, NH3 slip, and vehicle exhaust). Specifically, the Batch fractionation model was used to describe the partitioning of gaseous NH3 into particles and to trace the near-ground atmospheric NH3 sources. With the development of haze pollution, the dynamics of δ 15 N-NH4 + were generally consistent with the fractionation model. The simulated initial δ 15 N-NH3 values ranged from −22.6‰ to −2.1‰, suggesting the dominance of combustion-related sources for urban NH3 . These emission sources contributed significantly (92% on hazy days and 67% on clean days) to the total ambient NH3 in urban cities, as indicated by a Bayesian mixing model. Based on the Batch fractionation model, we concluded the following: 1) δ 15 N-NH4 + can be used to model the evolution of fine-mode aerosols and 2) combustion-related sources dominate the near-ground atmospheric NH3 in urban cities. These findings highlight the need for regulatory controls on gaseous NH3 emissions transported from local and surrounding industrial sources. Graphical abstract: Image 1 Highlights: δ 15 N-NH4 + values of PM2.5 in urban cities of NCP were higher on clean days than on hazy days. Simulated initial δ 15 N-NH3 values ranged from −22.6‰ to −2.1‰ based on a Batch model. Surface NH3 in the urban environment is dominated by combustion-related processes.